A Sociopragmatic Study of Saudi Arabic Address Terms: Implications for Cross-Cultural Communication - Ahmad I Alhojailan (Forum for Linguistic Studies, 2024)
Many studies have investigated terms of address, primarily focusing on Western languages. However, few studies have explored this topic in varieties of the Arabic language. This study examines the use of terms of address in Saudi Arabic, investigating the terms used by Saudi men and women, the effect of the addressees’ age and gender on the selection of address terms, and the linguistic patterns employed by Saudis when addressing each other. Twelve participants from two large cities in Saudi Arabia took part in the study. A semi-structured interview featuring 12 different social situations was conducted to answer the research questions. The interviews were conducted in the Saudi Arabic dialect to elicit authentic and realistic responses. The data were analyzed thematically to identify recurring patterns and trends in the use of address terms. Seven categories of address terms were identified. Furthermore, the age and gender of the addressees were found to influence the choice of terms. Moreover, five linguistic patterns were used by the participants to address each other. These findings provide important insights into professional settings where understanding suitable address terms can lead to more productive and culturally acceptable communication.